Fertilización inorgánica y orgánica su efecto en las características agronómicas y rendimiento del forraje Canavalia ensiformis L. en Zungarococha - Loreto - 2021 - Rucoba Celis, William Samuel (2022)
The research was carried out in a humid tropical forest, located in the district of San Juan Bautista, community of Zungarococha in Loreto – Peru. The area is from the National University of the Peruvian Amazon, faculty of agronomy, which is titled: INORGANIC AND ORGANIC FERTILIZATION ITS EFFECT ON AGRONOMIC CHARACTERISTICS AND FORAGE YIELD Canavalia ensiformis L. IN ZUNGAROCOCHA - LORETO - 2021, the data from field were taken at the eighth week of sowing, the design is a DBCA, in experimental units of 3 m x 1.2 (3.6 m2) with five treatments and six repetitions, the treatments under study were: T0 (control), T1 (10 tons of cuza /ha), T2 (20 tons of cuza /ha), T3 (100 kg 20N-20P-20K /ha) and T4 (200 20N-20P-20K /ha), resulting in the best treatment being the dose of 20 tons of guinea pig/ha, having the following results The results of treatment T2 (20 tons of guinea pig/ha), for a height of 0.97 meters, green matter of 1.87 kg/m2, dry matter of 0.41 kg/m2 and a percentage coverage of 91.67 percent. For yield, the T2 treatment (20 tons of cucumber/ha), which is 6.72 kilos per plot and 18,666.67 kilos per hectare.